Non-Linguistic Analysis of Call Center Conversations - Kopparapu, Sunil Kumar (Springer, 2015)
The book focuses on the part of the audio conversation not related to language such as speaking rate (in terms of number of syllables per unit time) and emotion centric features. This text examines using non-linguistics features to infer information from phone calls to call centers. The author analyzes "how" the conversation happens and not "what" the conversation is about by audio signal processing and analysis.